Pengaruh Motivasi Berdakwah terhadap Kemampuan Retorika Dakwah - Faisal Ahmadi (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
This study aims to determine the effect of motivation to preach against ability rhetoric of propaganda for the Friday prayer preacher. This research is quantitative descriptive correlational approach. Data collection techniques in this study using a questionnaire or a questionnaire given to 42 respondents. Respondents is the preacher who has a schedule in a mosque in the area of South Jakarta Setiabudi. Samples were selected based on purposive sampling technique or sample a particular purpose. Processing data using Pearson Product Moment Correlation. Conclusion the study shows there is influence between motivation to preach against the ability of propaganda rhetoric between motivational preaching influence on the ability categorized strong rhetorical (based on the correlation coefficient table), a significant, and positive.